PENGARUH TIPE KEPEMILIKAN DAN MANAJEMEN LABA TERHADAP PEMILIHAN KAP DAN PENETAPAN FEE AUDIT PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Anugerah Endriawan; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
This study aims to examine the factors of type of ownership and earnings management thatmay affect the selection of the firm and the determination of the audit fee on companies listed in Indonesia Stock Exchange (IDX). Factors that influence the selection of the firm and the audit fee is the type of ownership of the company is divided into a company that is majority owned by the government, as well as institutional company largely owned by the financial institution, and earnings management measured by discretionary accruals Modified Jones (2010).This study uses secondary data from financial statements companies listed in Indonesia Stock Exchange in 2011-2013. By using purposive sampling method obtained a sample of 132 financial statements of the company. This study used two regression, ie logistic regression and multiple linear regression. Before performing the multiple linear regression, the data first tested using the classical assumption testThe results of this study indicate that the type of ownership of state-owned enterprises, institutional and earnings management has no effect on the selection of public accounting firm as well as the type of state enterprises ownership and earnings management does not affect the audit fee. Variable types of institutional ownership and earnings management positive and significant impact on audit fees.